Study of Elementary School Teacher Communication Strategies in the Learning Process - Servista Bukit; Rini Ramadhani; Jelo Filo Bukit (Journal Corner of Education, Linguistics, and Literature, 2023)
Communication skills must be mastered by the teacher as a form of pedagogical competence. Through the communication skills possessed by the teacher, it is hoped that it can foster students' learning motivation to be active in learning so that they can improve their learning achievements. To create effective communication in learning, teachers must have a communication strategy. Communication strategy is a communication technique that is planned and used by the teacher in conveying learning material to students so that they are passionate about learning, want to ask questions of the teacher, and want to give opinions. This research focuses on knowing various teacher communication strategies in learning based on relevant research results. The results of this research study obtained several teacher communication strategies such as the use of verbal and non-verbal communication to carry out learning, creating two-way communication with students with the equalitarian style of communication, using communication media in the learning process, and giving rewards and punishments to participants. educate on the learning process. The results of this research study are expected to be a stimulus for teachers to determine communication strategies in learning as one of the teacher's efforts to create active and fun learning.